Free thiol groups in von Willebrand factor (VWF) are required for its full function under physiological flow conditions. (January 2016) - Solecka, Barbara A.; Weise, Christoph; Fuchs, Birte; Kannicht, Christoph
Abstract: Introduction: von Willebrand factor (VWF) is rich in cysteine; next to important structural disulfide bonds, free thiol groups are present. Free thiols on the surface of plasmatic VWF have been shown to play a role in VWF self-association and in platelet binding under pathologically high levels of shear stress. The present study explores the role of VWF free thiol groups under physiological levels of shear stress and in interactions with collagen and platelet-GPIbα receptor. Materials and methods: Free and accessible thiol groups were blocked with N-ethylmaleimide (NEM) and the derivatized molecule was evaluated in functional assays. Reduced cysteine residues were identified using biotin-linked maleimide (MPB) followed by analysis of multimer and domain incorporation and by analysis of derivatized tryptic peptides by mass spectrometry. Results: Blockade of free thiol groups significantly reduced VWF-mediated platelet recruitment to collagen under physiological flow conditions. This resulted from inhibition of VWF binding to both collagen and the platelet GPIb receptor. Evaluation of derivatization sites revealed a high level of derivatization in the cysteine-rich N - and C -termini of VWF. 19 MPB-derivatized peptides, 13 of which are described here for the first time, were identified by mass spectrometry. Conclusions: This study shows a significant contribution of free thiol groups in VWF to the mediation of platelet adhesion under physiological shear stress conditions. The free thiol groups are shown to be involved in VWF binding to both collagen III and platelet GP1b receptor. Highlights: Blockade of free thiol groups in VWF reduced platelet recruitment to collagen. Free thiol groups contribute to both VWF-collagen and VWF-GP1b binding under physiological shear conditions. Free thiol groups are distributed among all VWF multimers. 19 peptides containing unpaired cysteines were identified; 13 were previously unreported.